Tourists' cognitive image attributes of Kilim Karst Geoforest Park, Langkawi / Mohamad Hanif Mohamad Salleh and Mazlina Mahdzar. - Mohamad Salleh, Mohamad Hanif; Mahdzar, Mazlina (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
Geoparks has been gaining attention in Malaysia. This study aims to identify the attributes of cognitive image based on tourists’ perception of Kilim Karst Geoforest Park located in Langkawi Island, Malaysia. 384 questionnaires were collected at the study site. Data gathered was analysed using descriptive statistics and principle component analysis. Results suggest 13 attributes that form four dimensions of cognitive attributes; essential conditions, attractive condition, appealing activities and natural environment. This confirms the sub dimensions of cognitive attributes as proposed by previous researchers in a different setting. Theoretical and practical significance of the study is also provided.